Solid waste as a renewable resource : methodologies - Faria Albanese, Jimmy Alexander; Ruiz, M. Pilar (Apple Academic Press, 2015)
The twenty-first century world faces several enormous challenges: how to mitigate climate change, meet a growing energy demand without relying on fossil fuels, and manage the escalating quantities of solid waste generated by cities around the world. This compendium volume offers a viable solution to all three: using solid waste as a renewable resource.Intended for a wide audience ranging from engineers and academics to decision-makers in both the public and private sectors, this volume has gathered together research into a range of technologies and methodologies. The editors, two well-publishe.
Keywords: Recycling (Waste, etc.); Refuse and refuse disposal -- Management.; Compost.; Waste products as fuel.; elektronické knihy; electronic books